Analysis of The Influence of Economic Growth, Education and Unemployment Level on Poverty in The Special Region of Yogyakarta - Asmi, Rasylia Minatasya; Pratomo, Devanto Shasta (Journal of Development Economic and Social Studies, 2025)
In general, Indonesia's economic growth is dominated by Java at 57.05%. The large contribution from the island of Java proves that equitable development is progressing well. However, poverty still plagues the island of Java, especially the Special Region of Yogyakarta as the province with the highest poverty rate on the island of Java. This research aims to determine the effect of economic growth, education and unemployment rates on poverty in the Yogyakarta Special Region Province for the 2019-2023 period with data obtained from BPS and the method used is panel data regression. The research results show that economic growth, education and unemployment rates have a significant negative effect on poverty in the Special Region of Yogyakarta.